STUDI NUMERIK PENGARUH REYNOLDS NUMBER TERHADAP KARAKTERISTIK ALIRAN DAN PERPINDAHAN PANAS PADA SUSUNAN PIPA TIPE STAGGERED - Yusuf Yusuf (Politeknik Negeri Ketapang, 2021)
The characteristic of fluid-flow and heat-transfer on a circular cylinder with particular pattern is frequently used in various branches of modern technology today. The amount of heat transfer when fluid cureent passes through circular cylinder is expressed by Nusselt number parameter, eiter local Nusselt number (NuФ) or average Nusselt-number. Forced convection heat transfer on the circular cylinder with a staggered-type of using Reynolds-number (ReD) varied as the-value of 80, 200, 5000 while the tranverse-pitch (2D, 2D). The fluid inlet temperature entering shell is 350oK and the tube temperature is 300oK, which is modeled whith-Gambit 2.4.6 and simulated using Fluent-6.3.26 whith turbulent model k-w SST 2D steady-flow to obtain data related to the velocity profile and temperature distribution. From the simulation results obtained visualization contour of velocity, temperature and Nusselt number distribution. The smallest Nusselt value is at ReD 80 then ReD 200 and the highest is at ReD 5000.